2010
DOI: 10.1007/s00122-010-1422-6
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid origins of cultivated potatoes

Abstract: Solanum section Petota is taxonomically difficult, partly because of interspecific hybridization at both the diploid and polyploid levels. The taxonomy of cultivated potatoes is particularly controversial. Using DNA sequence data of the waxy gene, we here infer relationships among the four species of cultivated potatoes accepted in the latest taxonomic treatment (S. ajanhuiri, S. curtilobum, S. juzepczukii and S. tuberosum, the latter divided into the Andigenum and Chilotanum Cultivar Groups). The data support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 65 publications
2
36
0
2
Order By: Relevance
“…Separately, Rodríguez et al (2009) showed that although a dominant phylogeny using 12 nuclear orthologs supported the North and Central American B genome species as sister to the remaining clades in section Petota , a minority of these orthologs supported an alternative phylogeny with some South American species (members of the "Piurana" clade) as sister. In addition, recent nuclear ortholog DNA (GBSSI) sequence data ( Rodríguez et al 2010 ) showed the South American species S. circaeifolium (possessing white stellate corollas) to form a grade with the diploid North and Central B genome species, although grouping with A genome species in the plastid data ( Spooner et al 1991 ), suggesting that those few South American species possessing white stellate corollas (including S. morelliforme ) could be related to ancestral species in section Petota , rather than the B genome species from North and Central America.…”
Section: Utility Of Probabilistic Species Distribution Analyses-mentioning
confidence: 99%
“…Separately, Rodríguez et al (2009) showed that although a dominant phylogeny using 12 nuclear orthologs supported the North and Central American B genome species as sister to the remaining clades in section Petota , a minority of these orthologs supported an alternative phylogeny with some South American species (members of the "Piurana" clade) as sister. In addition, recent nuclear ortholog DNA (GBSSI) sequence data ( Rodríguez et al 2010 ) showed the South American species S. circaeifolium (possessing white stellate corollas) to form a grade with the diploid North and Central B genome species, although grouping with A genome species in the plastid data ( Spooner et al 1991 ), suggesting that those few South American species possessing white stellate corollas (including S. morelliforme ) could be related to ancestral species in section Petota , rather than the B genome species from North and Central America.…”
Section: Utility Of Probabilistic Species Distribution Analyses-mentioning
confidence: 99%
“…The latter species are known for their frost and drought tolerance and are also recognized for resistance to insect pests and late blight (Phytophthora infestans) (Martinez et al 2001;Browman 2003;Baldinelli 2014;Condori et al 2014). The frost tolerance of S. juzepczukii, S. curtilobum, and S. ajanhuiri can be traced to their wild progenitors: S. acaule and S. bolivense (Rodríguez et al 2010;Ovchinnikova et al 2011;Machida-Hirano 2015). Gene flow between wild and cultivated types is an important element of crop adaptation in their centres of origin (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Gene flow between wild and cultivated types is an important element of crop adaptation in their centres of origin (e.g. Rodríguez et al 2010;Hufford et al 2013;Mutegi et al 2015), and the role of crop wild relatives as a source of stress tolerance and resistance traits for crop breeding is well acknowledged (Hajjar and Hodgkin 2007;Jansky et al 2013). This study also revealed the value of hardy wild relatives of quinoa, cañahua, and potato as famine foods for Altiplano communities in periods of climate stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, Cai et al (2012) provided evidence that fen might be a combination of ver and jam or their progenitors. The species scr has long been recognized as a relative of tuberosum (Hawkes 1990;Rodríguez et al 2010).…”
Section: Introductionmentioning
confidence: 99%